The relationship between Human Resource Management Practices, Psychological Contract and Innovative Behaviours of Academicians - Supramaniam, Mahadevan; Muniandi, Taleselvi; T. , Ramayah; Kumar Moona Haji Mohamed, Ramesh; Subramaniam, Vinothiny; Begum, Mehrunishah (International Journal of Psychosocial Rehabilitation, 2020)
Innovative behavior is a behavior that directly and deliberately alters something by creating a different state from the current state of affairs. This can only happen if the employee is motivated and is associated with an employee’s psychological contract. While organizations are responsible for managing their human resource management such as recruitment and selection, employee training, performance appraisal, rewards, and incentives to fulfill this psychological contract. The purpose of this research is to test whether human resource management (HRM) practices have a positive impact on the fulfillment of psychological contracts to academics, which would enhance the innovative behavior of academic staff in private universities. Quantitative methods with stratified random sampling by supervisors of ten universities that have agreed to take part in this study have been conducted. The researchers only managed to collect as many as 183 samples, where the rate of reaction was 51%. However, only 165 responses were usable. The findings show that the innovative behavior of academic staff is associated with a psychological contract where it is influenced by human resource management practices. Only recruitment and selection are not significant in this study. The future recommendations of the study and the limitations of the study have been present in detail.